A review on the development of granulation technology in the past two decades - Chew, Yik Ling; Kahlous, Yahia; Uddin, A.B.M. Helal; Sarker, Zaidul Islam; Liew, Kai Bin (Research Trentz Academy Publishing Education Services, 2022)
Granulation is a technique that convert fine powder particles to granules which form appropriate agglomerate. It’s main function is to improve the powders flow and compressibility properties as well as to prevent segregation of the blend components. Traditionally, there are three types of granulation methods namely dry granulation, wet granulation and direct compressing. But, each one of these traditional methods has different disadvantage which prompted the researchers to modify and find new technique to granulate the powder. Among the new granulation technique are steam granulation, melt granulation, moisture activated dry granulation, foam granulation, pneumatic dry granulation technology and thermal adhesion granulation. Choosing a technique depends on the knowledge of advantages and disadvantages of each technique and how appropriate it is to the characteristics of each ingredient. This review mainly focusses on new techniques in granulation technologies for granules production.